Schistura alboguttata, a new loach species of the family Nemacheilidae (Pisces: Cypriniformes) from the Pearl River basin in Guangxi, South China - Cao, Liang; Zhang, E. (Zootaxa, 2018)
Schistura alboguttata, a new species of nemacheilid loach, is herein described from the Leli-He, a tributary flowing to the You-Jiang of the Pearl River basin (Zhu-Jiang in Chinese) at Tianlin County, Guangxi, South China. This new species can be readily distinguished from all other Chinese species of Schistura by its striking body coloration consisting of irregular white spots scattered over the dorsal and lateral regions of the body, with occasional irregular bars with narrow interspaces on the predorsal region.